African swine fever virus: a re-emerging threat to the swine industry and food security in the Americas (2022)
African swine fever (ASF) is a devastating disease for the swine industry, characterized by hemorrhagic fever with up to 100% mortality rate, and with a tremendous socioeconomic impact worldwide (Dixon et al., 2020). The disease was first reported in East Africa in the early 1920s as an acute hemorrhagic fever that caused the death of almost all infected domestic pigs (Montgomery, 1921; Plowright et al., 1969). Since then, the African swine fever virus (ASFV) has remained endemic in Africa affecting up to 35 African countries and has emerged in Europe, Asia, and now in the Americas